Hubungan Karakteristik Pasien dengan Kecemasan pada Pasien Gagal Jantung Kongestif di Ruang Rawat Inap RSU Dr. Slamet Garut - Sulastini Sulastini; Nita Fitria (STIKes Karsa Husada Garut, 2016)
In addition to physical problems, psychological problems also arise in patients with Congestive Heart Failure (CHF). One of the psychological problems that arise in patients with CHD is anxiety. Factors that can affect anxiety include age, gender, experience, self-concept, level of education, economic level and family support. On average, CHF patients treated at RSU dr. Slamet has 130 patients per month. The purpose of this study was to determine the characteristics of respondents and anxiety in patients with CHF in RSU dr. Slamet Garut. This type of research is quantitative with a cross sectional approach. The sampling technique uses concecutive sampling, with a sample of 23 respondents. Instrument to measure anxiety using the Hamilton Anxiety Rating Scale (HARS). The correlation test used is Pearson product moment. The results of this study indicate that age, gender, education, and occupation are not related to the anxiety level of CHF patients, with a significance value of 0.095 for age, 0.558 for type of kelami, 0.193 for education, and 0.842 for work (p> 0.05). The conclusion of this study is that there is no relationship between the characteristics of patients with anxiety in CHF patients.